Employee satisfaction in TM Call Centre: case study from the TM Call Centre employees in Kuching / Siti Sakinah Sam - Sam, Siti Sakinah (2010)
Currently, call centre have been aggressively find strategies to enhance the quality of service as a way to satisfy their employee and compete to be the best among others. This study tries to identify factors that influence employees’ satisfaction towards the organization since it is one of the most important in the Call Centre Kuching. Three variables will be investigate which are are factors, levels and strategies. A survey was carried out for the study and it involved all the employees in TM Call Centre in Kuching. A total of 140 questionnaires were collected and data was analyzed using SPSS version 16.0. Finding shows that majority are from Fault Department. This research findings has indicate that almost half of the employees are satisfy with the service offer by TM Call Centre.